Rare Association Between Neuroimmunological Diseases: A Possible Autoimmune Polyglandular Syndrome Type IV - de Araújo Tainá; Pastor Bandeira Isabelle; Fiuza Parolin Laura; Vinícius Magno Gonçalves Marcus (Journal of Clinical Case Reports and Images, 2020)
Autoimmune polyglandular syndromes (APS) are a diverse group of clinical conditions characterized by loss of immune tolerance in various tissues. This condition can be diagnosed in childhood or adulthood, with changes in the components of the disease throughout life. Here, an unusual case of association between immune-mediated diseases will be addressed: Myasthenia Gravis, Systemic Lupus Erythematosus, and Celiac Disease. In this patient, each disease was expressed over time. Finally, we assume that this is a clinical form of APS type IV, due to the lack of thyroid involvement to date.
Keywords: Neuroimmunological diseases